A pilot cohort study to assess the feasibility of HIV prevention science research among men who have sex with men in Dakar, Senegal. Issue 4 (2nd December 2013) - Dramé, Fatou Maria; Crawford, Emily E; Diouf, Daouda; Beyrer, Chris; Baral, Stefan D
Abstract : Introduction: Men who have sex with men (MSM) are disproportionately burdened by HIV in Senegal, across sub‐Saharan Africa and throughout the world. This is driven in part by stigma, and limits health achievements and social capital among these populations. To date, there is a limited understanding of the feasibility of prospective HIV prevention studies among MSM in Senegal, including HIV incidence and cohort retention rates. Methods: One hundred and nineteen men who reported having anal sex with another man in the past 12 months were randomly selected from a sampling frame of 450 unique members of community groups serving MSM in Dakar. These men were enrolled in a 15‐month pilot cohort study implemented by a community‐based partner. The study included a structured survey instrument and biological testing for HIV, syphilis and hepatitis B virus at two time points. Results: Baseline HIV prevalence was 36.0% (43/114), with cumulative HIV prevalence at study end being 47.2% (51/108). The annualized incidence rate was 16% (8/40 at risk for seroconversion over 15 months of follow‐up, 95% confidence interval 4.6–27.4%). Thirty‐seven men were lost to follow up, including at least four deaths. Men who were able to confide in someone about health, emotional distress and sex were less likely to be HIV positive (OR 0.36, p < 0.05, 95% CI 0.13, 0.97). Conclusions: High HIV prevalence and incidence, as well as mortality in this young population of Senegalese MSM indicate a public health emergency. Moreover, given the high burden of HIV and rate of incident HIV infections, this population appears to be appropriate for the evaluation of novel HIV prevention, treatment and care approaches. Using a study implemented by community‐based organizations, there appears to be feasibility in implementing interventions addressing the multiple levels of HIV risk among MSM in this setting. However, low retention across arms of this pilot intervention, and in the cohort, will need to be addressed for larger‐scale efficacy trials to be feasible.